1998
DOI: 10.1116/1.589966
|View full text |Cite
|
Sign up to set email alerts
|

Eu:CaF 2 layers on p-Si(100) grown using molecular beam epitaxy as materials for Si-based optoelectronics

Abstract: Articles you may be interested inEpitaxial growth and strain relaxation of Ba Ti O 3 thin films on Sr Ti O 3 buffered (001) Si by molecular beam epitaxy J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…19 Further study on the full-color simulation and up-conversion emission in the multi-doped cubes is still in progress. These luminescent properties showed that these nanocubes with tunable size distribution and truncation degree can be functionalized with ease, and might find applications in many fields, such as biological labels, 12 visible electroluminescent devices, 16,17 as well as chromaticitic controllable advanced flat-panel display applications. 20 This work was supported by NSFC (20025102, 50028201, 20151001), the Foundation for the Author of National Excellent Doctoral Dissertation of P. R. China, and the state key project of fundamental research for nanomaterials and nanostructures.…”
Section: T H I S J O U R N a L I S © T H E R O Y A L S O C I E T Y O ...mentioning
confidence: 96%
See 1 more Smart Citation
“…19 Further study on the full-color simulation and up-conversion emission in the multi-doped cubes is still in progress. These luminescent properties showed that these nanocubes with tunable size distribution and truncation degree can be functionalized with ease, and might find applications in many fields, such as biological labels, 12 visible electroluminescent devices, 16,17 as well as chromaticitic controllable advanced flat-panel display applications. 20 This work was supported by NSFC (20025102, 50028201, 20151001), the Foundation for the Author of National Excellent Doctoral Dissertation of P. R. China, and the state key project of fundamental research for nanomaterials and nanostructures.…”
Section: T H I S J O U R N a L I S © T H E R O Y A L S O C I E T Y O ...mentioning
confidence: 96%
“…Since CaF 2 is a widely used host material for rare earth ions, 11,16,17 a functionalization approach was undergone on the nanocubes by a solution-based chemical modifying process. Bright red or green luminescence was observed for Eu(III) or Tb(III) doped CaF 2 nanocrystals, respectively.…”
Section: T H I S J O U R N a L I S © T H E R O Y A L S O C I E T Y O ...mentioning
confidence: 99%
“…On Si(1 1 1), CaF 2 grows with an atomically flat (1 1 1) surface [4]. On Si(0 0 1) and at a growth temperature of about 750°C, CaF 2 growth is strongly anisotropic because of the formation of ridges and grooves which run along the [1 1 0] direction of the substrate [5][6][7][8]. The fluorite ridges are characterized by {1 1 1} facets with the CaF 2 lattice being oriented with its [1 1 0] axis perpendicular to the surface plane.…”
Section: Introductionmentioning
confidence: 99%
“…Epitaxial layers and nanostructures of strontium and calcium fluorides are interesting for basic studies of low dimensional effects and, doped with rare-earth ions, are quite attractive for applications in optoelectronics. 6 Moreover, the heteroepitaxial growth of fluorides has recently received considerable attention for possible applications in silicon based resonant tunneling devices. 7,8 Because of the formation of sharp and stable interfaces, fluorides could also find interesting applications as buffer layers in ultrathin semiconductor-insulator systems based on wide gap materials such as rare-earth oxides, preventing the oxidation of the semiconductor substrate.…”
Section: Introductionmentioning
confidence: 99%